The complete mitochondrial genome and phylogenetic analysis of Euurobracon yokahamae (Hymenoptera: Braconidae). Issue 6 (3rd June 2022) - Kim, Wanggyu; Byun, Hye-Woo; Jeon, Mi-Jeong
Abstract: Euurobracon yokahamae is a parasitoid wasp found solely in Asia, and is endangered in some countries. The complete mitochondrial DNA sequence of E. yokahamae was sequenced using next-generation sequencing (NGS). The mitogenome of this species is 14, 974bp long and encodes for 13 protein-coding genes (PCGs), 22 transfer RNAs, and 2 ribosomal RNAs. Maximum likelihood phylogenetic analysis of the mitochondrial genome of braconid species was performed. Tree topology showed that E. yokahamae was closely related to another species of the same genus.